Effect of linseed diet and hazelnut skin supplementation on oxidative status and blood serum metabolites in rabbits - Candellone, Alessia; Peiretti, Pier Giorgio; Binello, Arianna; Bergagna, Stefania; Meineri, Giorgia (Progress in Nutrition, 2019)
Rabbits in groups of eight were fed for nine weeks with diets containing linseed, rich in polyunsaturated fatty acids (LS), linseed plus hazelnut skins, with antioxidant function (LS+HS), or palm oil, rich in saturated fatty acids (PO).  The aim of this work was to compare the effects of aforementioned diets on serum biochemical parameters related to nutritional and inflammatory status, immune function and oxidative balance [triglycerides, cholesterol, alanine aminotransferase (ALT), aspartate aminotransferase (AST), lysozyme, reactive oxygen species and antioxidant power, respectively]. At the end of the study redox imbalance (with a significant increase in oxidative stress and decrease in antioxidant defenses) was greatest in rabbits fed the LS diet (without additional antioxidant protection) compared to the other two groups  (P